In vivo armed macrophages curb liver metastasis through tumor-reactive T-cell rejuvenation - Marco Notaro; Maristella Borghetti; Chiara Bresesti; Giovanna Giacca; Thomas Kerzel; Carl Mirko Mercado; Stefano Beretta; Marco Monti; Ivan Merelli; Silvia Iaia; Marco Genua; Andrea Annoni; et al. (Nature Communications)
Abstract Despite recent progress in cancer treatment, liver metastases persist as an unmet clinical need. Here, we show that arming liver and tumor-associated macrophages in vivo to co-express tumor antigens (TAs), IFNα, and IL-12 unleashes robust anti-tumor immune responses, leading to the regression of liver metastases. Mechanistically, in vivo armed macrophages expand tumor reactive CD8+ T cells, which acquire features of progenitor exhausted T cells and kill cancer cells independently of CD4+ T cell help. IFNα and IL-12 produced by armed macrophages reprogram antigen presenting cells and rewire cellular interactions, rescuing tumor reactive T cell functions. In vivo armed macrophages trigger anti-tumor immunity in distinct liver metastasis mouse models of colorectal cancer and melanoma, expressing either surrogate tumor antigens, naturally occurring neoantigens or tumor-associated antigens. Altogether, our findings support the translational potential of in vivo armed liver macrophages to expand and rejuvenate tumor reactive T cells for the treatment of liver metastases.